2018
DOI: 10.1029/2018gl077842
|View full text |Cite
|
Sign up to set email alerts
|

The September 2017 SEP Event in Context With the Current Solar Cycle: Mars Express ASPERA‐3/IMA and MAVEN/SEP Observations

Abstract: We use Mars Atmosphere and Volatile Evolution/Solar Energetic Particle (MAVEN/SEP) data to estimate the ranges of particle energies that generate background noise in the Analyzer of Space Plasmas and Energetic Atoms‐3/Ion Mass Analyzer (IMA) instrument on Mars Express. The particles that generate IMA background counts are estimated to be electrons with energies >1 MeV and protons >20 MeV. The September 2017 event at Mars resulted in the strongest flux of energetic particles measured by MAVEN/SEP. We correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…In the following, italicVartrue¯0 is the average solar parameter at a time t 0 before the periapsis and italicVartrue¯1 is the average solar parameters at a time t 1 after the periapsis. We then linearly interpolated the reconstructed solar wind parameters from italicVartrue¯0 and italicVartrue¯1 to the time t when we reconstructed the precipitating ion flux (as in section ) using the following relation: 0.25emVar=italicVartrue¯0+()italicVartrue¯1italicVartrue¯0*tt0t1t0 In order to estimate an uncertainty for these reconstructed solar wind parameters, we considered the dispersion of the reconstructed solar wind values at t 0 and t 1 . To verify the validity of our methods, we also compared these results with Mars Express measurements of the density and speed of the solar wind using ASPERA‐3 (Barabash et al, ; Ramstad et al, ). In Figure , we displayed our interpolated solar wind parameters (in orange) and the Mars Express measured values (in blue): the solar wind density (Figure a) and the solar wind speed (Figure b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following, italicVartrue¯0 is the average solar parameter at a time t 0 before the periapsis and italicVartrue¯1 is the average solar parameters at a time t 1 after the periapsis. We then linearly interpolated the reconstructed solar wind parameters from italicVartrue¯0 and italicVartrue¯1 to the time t when we reconstructed the precipitating ion flux (as in section ) using the following relation: 0.25emVar=italicVartrue¯0+()italicVartrue¯1italicVartrue¯0*tt0t1t0 In order to estimate an uncertainty for these reconstructed solar wind parameters, we considered the dispersion of the reconstructed solar wind values at t 0 and t 1 . To verify the validity of our methods, we also compared these results with Mars Express measurements of the density and speed of the solar wind using ASPERA‐3 (Barabash et al, ; Ramstad et al, ). In Figure , we displayed our interpolated solar wind parameters (in orange) and the Mars Express measured values (in blue): the solar wind density (Figure a) and the solar wind speed (Figure b).…”
Section: Methodsmentioning
confidence: 99%
“…In order to estimate an uncertainty for these reconstructed solar wind parameters, we considered the dispersion of the reconstructed solar wind values at t 0 and t 1 . To verify the validity of our methods, we also compared these results with Mars Express measurements of the density and speed of the solar wind using ASPERA-3 (Barabash et al, 2006;Ramstad et al, 2018). In Figure 2, we displayed our interpolated solar wind parameters (in orange) and the Mars Express measured values (in blue): the solar wind density (Figure 2a) and the solar wind speed (Figure 2b).…”
Section: Reconstruction Of the Solar Conditions During Maven Periapsimentioning
confidence: 98%
“…Effects of the solar storms on Mars and its surrounding space environment were also significant. The September 2017 event produced the largest SEP event seen by MAVEN since its arrival at Mars in 2014 and the fourth largest seen by Mars Express since its arrival at Mars in 2004 (Ramstad et al., 2018). SEPs significantly enhanced nightside ionosphere densities, producing peak electron densities of 1–2 × 10 4 cm −3 around 120 km altitude (Harada et al., 2018).…”
Section: Solar Storms Of September 2017 and Their Effects At Earth Anmentioning
confidence: 99%
“…The overall trend follows observations from MAVEN/SWEA and also MAVEN/SEP‐FTO (Figure c). Ramstad et al () reported the first attempt to calibrate the IMA penetrating background counts with the MAVEN/SEP‐FTO data. In doing so, they found that the IMA background counts are due to >1 MeV SEP electrons and >20 MeV protons.…”
Section: Seps At Marsmentioning
confidence: 99%